2022
DOI: 10.1002/ps.6859
|View full text |Cite
|
Sign up to set email alerts
|

Facile pathway to construct mesoporous silica nanoparticles loaded with pyraclostrobin: Physicochemical properties, antifungal activity, and biosafety

Abstract: BACKGROUND A controlled‐release formulation based on mesoporous silica nanoparticles (MSNs) provides an effective way for reducing pesticide use and protecting the ecological environment. In this study, MSNs loaded with pyraclostrobin (PYR@MSNs) were prepared using a one‐pot method. RESULTS The characteristics of PYR@MSNs were systematically investigated, including morphology, loading content, ultraviolet (UV) resistance, release behavior, control effects against pathogens, and safety to nontarget organisms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…129 Nanotechnology can offer ecofriendly and green alternatives for plant disease control, and the use of nanotechnology to develop safe antifungal agents is of great significance. [129][130][131][132][133][134] Nanobiofungicides are fungicides formulated at the nanometer size with novel properties and can be designated as nanohybrids or nanocomposites. 135,136 It has been reported that microorganisms (including bacteria, fungi, actinomyces, yeast, and algae) and plants are able to synthesize nanofungicides, [137][138][139] and the biosynthesis of nanofungicides has been recognized as an efficient and green method.…”
Section: Nanotechnology In Fungicidesmentioning
confidence: 99%
“…129 Nanotechnology can offer ecofriendly and green alternatives for plant disease control, and the use of nanotechnology to develop safe antifungal agents is of great significance. [129][130][131][132][133][134] Nanobiofungicides are fungicides formulated at the nanometer size with novel properties and can be designated as nanohybrids or nanocomposites. 135,136 It has been reported that microorganisms (including bacteria, fungi, actinomyces, yeast, and algae) and plants are able to synthesize nanofungicides, [137][138][139] and the biosynthesis of nanofungicides has been recognized as an efficient and green method.…”
Section: Nanotechnology In Fungicidesmentioning
confidence: 99%
“…Similar results of lower toxicity from PSNdelivered pesticide on earthworms were also found on several other studies. 82,83 Further, several studies reported reduced phytotoxicity of PSN-delivered pesticides in terms of chromosome aberration (CA) and mitotic index (MI), where a lower CA and higher MI indicate safer molecules. The Vicia faba chromosomal aberration indexes of lambda cyhalothrin EC were 0.21, 0.25, and 0.31 at concentrations of 10, 50, and 100 mg/L, whereas those of dopamine-conjugated MSN-encapsulated lambda cyhalothrin were 0.04, 0.05, and 0.06, respectively, at the same concentration.…”
Section: Improved Pest Control Efficacymentioning
confidence: 99%
“…Several studies have also reported lower apoptosis rates of PSN-delivered pesticides compared to conventional formulations. 82,83 Thus, the sustained cell viability with lower apoptosis rate demonstrates that PSNs are a safer nanocarrier for both pesticide applicators and neighbors.…”
Section: Improved Pest Control Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were allowed to stain at 4 °C for 15 min in the dark. [57][58][59] 3 RESULTS AND DISCUSSION…”
Section: L02 Cell Apoptosismentioning
confidence: 99%